Analisis Multilevel Faktor Berbasis Health Belief Model Terhadap Keterpaparan Covid-19 Pada Radiografer di Wilayah Jawa Timur - Adhi Artono (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: The situation of the Covid-19 pandemic is a lesson for Indonesia, especially in the field of health. Problems in the field of health are increasingly evident in the era of the Covid-19 pandemic. The use of PPE is the lowest level of control because it is difficult to obtain when its use is massive, often inappropriate selection and way of use, uncomfortable so it requires compliance supervision and accuracy of use, and in some ways can affect the work process. Judging from the importance of the use of personal protective equipment for radiographers, researchers want to know the influence of health belief model-based factors on the high exposure of Covid-19 on radiographers in East Java.Methods: Design observational research with a cross-sectional approach. The population of all hospitals in East Java region is 152 people. A sample of all 110 radiographers with proportional random sampling techniques. Independent variables are predisposing factors (age, gender, education level, knowledge and length of work), reinforcing factors (policies and assessments) and enabling factors (availability of PPE). Variable dependent exposure of Covid-19 on radiographers in East Java region. The analyses used are univariate, bivariate and multilevel analysis.Results: The results showed that hospital-type conditions had a low contextual influence on the variation in exposure to covid 19 in radiographers by 12.49%. The relationship value shows the number p = 0.341, which means insignificant. The table also showed a likelihood ratio = 0.0043 meaning that there was no statistically significant difference between the models without taking into account contextual influences and models that took into account contextual influences. In this case, the type of hospital.Conclusions: This research is expected to increase knowledge or input and consideration in research related to Covid-19 exposure to radiographers.